1997
DOI: 10.1046/j.1471-4159.1997.68041372.x
|View full text |Cite
|
Sign up to set email alerts
|

Four 5‐Hydroxytryptamine7 (5‐HT7) Receptor Isoforms in Human and Rat Produced by Alternative Splicing: Species Differences Due to Altered Intron‐Exon Organization

Abstract: The serotonin (5-HT) 5-HT7 receptor subtype is thought to mediate a number of physiological effects in mammalian brain and periphery. Previous studies suggested that alternative splicing might contribute to 5-HT7 receptor diversity as well. We now report that alternative splicing in human and rat tissues produces four 5-HT7 receptor isoforms that differ in their predicted C-terminal intracellular tails. Human and rat partial 5-HT7 cDNAs and intronic sequences were identified and compared. In rat tissues, three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
117
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(132 citation statements)
references
References 20 publications
12
117
0
Order By: Relevance
“…50 The current data confirm and extend on previous pharmacological 26,27 and mRNA expression studies that suggested the existence of multiple muscarinic receptors on blood lymphocytes. 33,63,51,52 While mRNA for m3, m4, and m5 receptors has been reported in mononuclear cells, the additional detection of m3 and m4 mRNA in neutrophils and stromal cells remains a novel finding. Acetylcholine synthesis and release from T-lymphocytes via muscarinic receptors have been documented; 53 however, such stimulation of muscarinic receptors on stromal cells by direct contact through adhesion molecules remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 The current data confirm and extend on previous pharmacological 26,27 and mRNA expression studies that suggested the existence of multiple muscarinic receptors on blood lymphocytes. 33,63,51,52 While mRNA for m3, m4, and m5 receptors has been reported in mononuclear cells, the additional detection of m3 and m4 mRNA in neutrophils and stromal cells remains a novel finding. Acetylcholine synthesis and release from T-lymphocytes via muscarinic receptors have been documented; 53 however, such stimulation of muscarinic receptors on stromal cells by direct contact through adhesion molecules remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62][63] Primers and conditions used for amplification of the d4 receptor were as previously published. 32 In addition, primers were not designed within known polymorphic coding regions such as for the 5ht2a and 5ht6 receptors.…”
Section: Rna Extraction and First Strand Cdna Synthesismentioning
confidence: 99%
“…Many GPCRs have isoforms with di ering C-terminal tails. These include the prostaglandin EP3 receptor Hasegawa et al, 1996;Jin et al, 1997;Irie et al, 1993), a 1A -AR (Chang et al, 1998;Hirasawa et al, 1995), serotonin 5HT 4 (Gerald et al, 1995) and 5HT 7 receptors (Heidmann et al, 1997), and the somatostatin SSTR 2 receptor (Vanetti et al, 1993;Schindler et al, 1998). Most splice variants share similar pharmacology, but some show marked di erences in signalling properties.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-HT receptors, each encoded by a separate gene, have been grouped into families called 5-HT 1 to 5-HT 7 , with some of the families containing several members. The human serotonin receptors 5-HT 4 and 5-HT 7 couple to the heterotrimeric G protein G s and exist in multiple splice variants (10,11). Stimulation of these receptors leads to activation of adenylyl cyclase and a rapid increase in the formation of the intracellular second messenger cAMP.…”
mentioning
confidence: 99%